Utilization of Bacillus subtilis (Cohn, 1872) and Neos-A as probiotics in the diet of GIFT tilapia - Wong, Kim Yan (2013)
An experiment on the utilization of Bacillus subtilis and Neos-A as probiotics in diet of GIFT (Genetic Improved Farmed Tilapia) was carried.out. This experiment was conducted for 12 weeks at Wet Laboratory of the Department of Aquaculture, Faculty of Agriculture, University Putra Malaysia. The objective of this study was to determine the growth performance of fingerling GIFT fed with probiotic feed. Fingerlings with initial size ranged between 3 cm to 6 cm were used. Probiotic B.subtilis L10 strain and Neos-A were mixed with a commercial pellet. After feeding for 12 weeks, there were no significant differences (P>0.05) among treatments for growth performance of fish in both treatment. It was concluded that GIFT fish did not require probiotic in diets.